Exploring the Perceptual Effects of Uniforms and Accoutrements Among a Sample of Police Officers: The Locker Room as a Site of Transformation. (28th February 2022) - Simpson, Rylan; Sargeant, Elise
Abstract: The effects of officer appearance on public perceptions of police have been the subject of considerable scholarly attention. Little known research, however, has explored such effects on officers' perceptions of each other. As part of the present research, we complement previous literature by testing the perceptual effects of uniforms and accoutrements among a sample of sworn police officers ( N = 238) from the Queensland Police Service. Our results reveal that different types of attire (e.g. uniform or civilian), different styles of uniforms (e.g. light blue shirt or dark blue shirt), different accoutrements (e.g. high-visibility vest or sunglasses), and different bodily manipulations (e.g. sleeve tattoo) can impact officers' perceptions of each other along various outcomes, including accountability, aggression, approachability, competency, friendliness, intimidation, professionalism, respectfulness, and trustworthiness. We discuss our results with respect to policing research, policy, and practice.